If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6s + 2 = 6s + -9 Reorder the terms: 2 + 6s = 6s + -9 Reorder the terms: 2 + 6s = -9 + 6s Add '-6s' to each side of the equation. 2 + 6s + -6s = -9 + 6s + -6s Combine like terms: 6s + -6s = 0 2 + 0 = -9 + 6s + -6s 2 = -9 + 6s + -6s Combine like terms: 6s + -6s = 0 2 = -9 + 0 2 = -9 Solving 2 = -9 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 2x-64=48 | | 1/48x^2-1/16=0 | | 2/3x=4y+3 | | 8x+7-10x=11 | | (1-9/X)^2=16/25 | | -3/10=n/15 | | 17x^2+18x-19=0 | | 7x^2-2x-5= | | 8n-(3n+9)= | | 6/3*2+7-5 | | 11/x+10=x | | 6/3x2+7-5 | | 5/12+1/15 | | p=2qr+2qs | | x^2y-3xy-x^2+2y-3x-2=0 | | 3/4(x+2)-1 | | 2y^2-5y+2= | | (x+7)(x+4)(x-8)=0 | | 3z^2-19z-14= | | 81=1/2(18)(x+7) | | (x+7)(x+4)(x-8)=8 | | 162=18(a+14) | | 2t+4=11-t | | 162=18(2a+14) | | 15=-9x+50 | | x^5-9x^4+34x^3-66x^2+65x-25=0 | | K+1/6=4K+1/6 | | 2x-1+3=x-3x-1 | | 6x+1=3(2x+1)-x+4 | | 15r^2+8-16= | | 4x^2+12-40= | | 4-6x=-5 |